PESANTRENPRENEUR AS AN AGENT OF ECONOMIC TRANSFORMATION: A SOCIAL ENTREPRENEURSHIP MODEL BASED ON ISLAMIC VALUE - Ahmad Saef Alfath; Nikmatul Masruroh (Journal of Global Business and Management Review, 2026)
This study aims to analyze the role of pesantrenpreneurs as agents of economic transformation based on Islamic values and to construct a model of social entrepreneurship within the pesantren environment. The study employs a qualitative approach using a case study design at the Darussalam Blokagung Pesantren in Banyuwangi. Data were collected through semi-structured interviews, participatory observation, and documentation, involving administrators, business managers, students, and stakeholders selected through purposive and snowball sampling. The results reveal four main themes: the internalization of Islamic values in entrepreneurship, the role of students as agents of change, a business model based on social impact, and the limitations of measuring social impact. The findings indicate that pesantrenpreneurs are capable of integrating spiritual, educational, and economic dimensions in a sustainable manner, although they are not yet supported by an evaluation system such as SROI. This study contributes to the development of Islamic social entrepreneurship and provides practical implications for strengthening business models and social impact evaluation in Islamic boarding schools.